The impact of engagement in sport on graduate employability: implications for higher education policy and practice. Issue 3 (3rd July 2017) - Griffiths, Kerry; Bullough, Steve; Shibli, Simon; Wilson, Jayne
ABSTRACT: This paper analyses the impact of engagement in sport on graduate employability using a triangulation of views from three key stakeholder groups. Primary research was conducted with 5838 graduates, 112 employers and 13 university senior executives as part of a mixed-methods approach. The research found that engagement in sport was viewed as a sound investment from the perspectives of all three groups, with examples highlighting how sport provided 'added value' beyond subject-specific qualifications. This finding was particularly prominent where graduates demonstrated experience of voluntary roles through the leadership and management of sport and could articulate how this had a positive impact on the development of additional employability attributes. We argue that there are important implications for higher education policy, sports policy, universities, employers and students. For students, employability can be enhanced through participation and volunteering in sport, which is shown to be a good investment in terms of both skill development and future earnings. For employers, when recruiting graduates, a history of sport participation (inclusive of voluntary experience) may be a good indicator of candidates with desirable traits for employment. For universities, meeting their customers' demand for sport with sufficient supply through strategic investment is an important consideration of their offer.